Rehabilitasi Mental Berbasis Komunitas terhadap Kualitas Hidup ODGJ - Neni Rochmayati Satuhu; Neti Juniarti; Efri Widianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to map community-based mental rehabilitation on the quality of life of ODGJ in primary care settings. This research method uses the Scoping Review research method. A literature search was done by searching Pubmed, Scopus, Ebsco, and Google Scholar. The search uses Severe Mental Illness (SMI), Community Based Rehabilitation, and Quality Of Life. The results showed that most community-based mental rehabilitation could improve the quality of life for ODGJ, including schizophrenic, schizoaffective, bipolar, and psychotic. This also affects the quality of life of families/caregivers. The types of rehabilitation provided include psychoeducation and social training, balancing everyday life (BEL), self-management programs, emotional management, instilling hope, mindfulness, progressive muscle relaxation, physical activity training, and peer support. In conclusion, the review results can help increase the capacity of mental health programs in the community. They can be effectively applied in developing community mental health rehabilitation therapy. Keywords: Quality of Life, Severe ODGJ, Community Rehabilitation